2020
DOI: 10.1186/s12884-020-2727-3
|View full text |Cite
|
Sign up to set email alerts
|

Identifying risk factors for perinatal death at Tororo District Hospital, Uganda: a case-control study

Abstract: Background: Sub-Saharan Africa faces a disproportionate burden of perinatal deaths globally. However, data to inform targeted interventions on an institutional level is lacking, especially in rural settings. The objective of this study is to identify risk factors for perinatal death at a resource-limited hospital in Uganda. Methods: This is a retrospective case-control study at a district hospital in eastern Uganda using birth registry data. Cases were admissions with stillbirths at or beyond 24 weeks or neona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
1
4
0
2
Order By: Relevance
“…Even with the supervision of a trained health worker, vaginal deliveries may have higher risks of perinatal deaths than operative deliveries. This could be because of malpresentations that may not be easily corrected due to limited time for manipulation, emergency deliveries when there are pregnancy complications like pre-eclampsia and eclampsia, multiple gestation, and preterm deliveries resulting in adverse outcomes [31,32]. This observation is similar to findings from other studies including a study conducted in Ghana which showed a 5.9% prevalence of stillbirths among women who had delivered vaginally [31].…”
Section: Discussionsupporting
confidence: 83%
“…Even with the supervision of a trained health worker, vaginal deliveries may have higher risks of perinatal deaths than operative deliveries. This could be because of malpresentations that may not be easily corrected due to limited time for manipulation, emergency deliveries when there are pregnancy complications like pre-eclampsia and eclampsia, multiple gestation, and preterm deliveries resulting in adverse outcomes [31,32]. This observation is similar to findings from other studies including a study conducted in Ghana which showed a 5.9% prevalence of stillbirths among women who had delivered vaginally [31].…”
Section: Discussionsupporting
confidence: 83%
“…Increased risk of perinatal death was associated with a low level of maternal education, rural residence, <4 ANC visits, PPH, placental abruption, LBW delivery, the child’s sex, and referral for delivery [ 45 ]. Prematurity, a low birth weight, breech presentation, multiple gestation, and cesarean delivery reduce preventability goals related to perinatal death [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data and the approach used to acquire them can be used to inform interventions aimed at reducing the rate of stillbirths and neonatal deaths in non-developed, developing, and developed countries that, even with low perinatal mortality rates, are influenced by factors that characterize the deaths [ 13 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women of Afro-Caribbean and Asian origin are more at risk of stillbirths 7,[11][12][13][14] and this may be associated with racial disparities in accessing health care 12 . Incidence of stillbirth in Uganda is about 2.0% − 3.6% 15,16 . However, due to challenges in access to care and policies on death registration in the global south, most stillbirths are not registered 17 .…”
Section: Introductionmentioning
confidence: 99%